Soccer training load research mapping and trends: a bibliometric analysis - Tommy Apriantono; Muhamad Fahmi Hasan; Nia Sri Ramania; Rini Syafriani; Kusnaedi Kusnaedi; Didi Sunadi; Samsul Bahri; Agung Dwi Juniarsyah; Gifran Rihla Gifarka Latief; Qintarazany M. Elhaque; Rifqi Festiawan; Yudhi Teguh Pambudi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
In soccer, monitoring training load is crucial for performance enhancement, optimizing recovery, and preventing injury risks. The research trend in training load within soccer has been rapidly evolving, making this bibliometric study instrumental in understanding the direction of research focus in soccer training load. The objective of this study is to comprehend and explore the current state of research on soccer training load. This research analysis includes mapping contributions by country, publication years, authors, articles, and their respective citation counts. Findings indicate that research on training load in soccer commenced as early as 1976 and has gradually expanded with time, with a significant increase observed in 2019, marked by 109 articles addressing training load in soccer. The United Kingdom emerges as the top country in terms of scholarly publications and citation counts in this field.